2020
DOI: 10.1002/ana.25950
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome‐Based Drug Discovery Paradigm for Neurodevelopmental Disorders

Abstract: Advances in genetic discoveries have created substantial opportunities for precision medicine in neurodevelopmental disorders. Many of the genes implicated in these diseases encode proteins that regulate gene expression, such as chromatin‐associated proteins, transcription factors, and RNA‐binding proteins. The identification of targeted therapeutics for individuals carrying mutations in these genes remains a challenge, as the encoded proteins can theoretically regulate thousands of downstream targets in a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 88 publications
(159 reference statements)
0
14
0
Order By: Relevance
“…The convergence of genes and genic sub-regions between these two disease areas suggest that similar biological processes play a fundamental role in these two groups of phenotypes. Indeed, cellular proliferation, chromatin remodeling, cell migration, and other cancer-relevant processes have been implicated in neurodevelopmental diseases (De Rubeis et al, 2014;Dhindsa et al, 2021;Feng et al, 2019;Kaplanis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The convergence of genes and genic sub-regions between these two disease areas suggest that similar biological processes play a fundamental role in these two groups of phenotypes. Indeed, cellular proliferation, chromatin remodeling, cell migration, and other cancer-relevant processes have been implicated in neurodevelopmental diseases (De Rubeis et al, 2014;Dhindsa et al, 2021;Feng et al, 2019;Kaplanis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Network analysis suggested that RASopathy proteins participate in 33 pathways ( 111 ). Inclusion of drugs acting on chromatin modifiers, such as statins and histone deacetylase inhibitors, may have a better chance ( 71 ); however, contending with toxicity remains a challenge ( 129 ). Last, with the advent of the impact of artificial intelligence (AI), the question has been raised as to whether AI can offer a breakthrough in predicting risks and prognosis for neurodevelopmental disorders ( 130 ) and drug repurposing ( 131 ).…”
Section: Concluding Remarks: Cancer Neurodevelopmental Disorders Pharmacology and The Ultimate Aim Of Measurementsmentioning
confidence: 99%
“…Unfortunately, sulforaphane exhibits somewhat poor pharmacokinetics that limit its utility in humans ( 72 , 73 ). To screen for candidate alternatives to sulforaphane, we adapted a transcriptome-guided drug discovery scheme termed transcriptome reversal ( 74 , 75 ). Transcriptome reversal posits that if a dysregulated transcriptome drives a particular disease, then correcting the transcriptome back toward a normal state may be therapeutic.…”
Section: Resultsmentioning
confidence: 99%